Descriptive Reference Fixing and Epistemic Privileges - Ruffino, Marco (Aufklärung: journal of philosophy, 2021)
Donnellan (1977) argues for a radical limitation of Kripke’s (1980) thesis concerning the possibility of contingent truths knowable a priori as a result of descriptive reference fixing for names. According to the former, in the absence of some form of acquaintance between the speaker and the object of knowledge, there can be no de re singular knowledge (or even belief) envisaged by Kripke. And in the presence of acquaintance (which typically takes the form of perceptual contact), there can be no a priori knowledge. On the other hand, Jeshion (2001) argues that Donnellan’s main argument is fundamentally flawed. She explores a loophole intentionally (and explicitly) left open by Donnellan to say that he has not ruled out an alternative explanation for the problem that motivates the revision of Kripke’s thesis. In this paper, I access Jeshion’s argument against Donnellan. As I intend to show, she does not fully appreciate a second loophole in Donnellan’s account that offers a more appropriate way of seeing Kripke’s examples.